Air pollution reference measurement methods and systems : proceedings of the international workshop, Bilthoven, December 12-16, 1977 - Schneider, T. (Tonny), 1935-; Koning, H. W. de.; Brasser, L. J.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier Scientific Pub. Co. ; New York : Distributors for the U.S. and Canada, Elsevier/North-Holland, 1978)
Proceedings of the international workshop, Bilthoven, December 12-16, 1977 / organised by the National Institute of Public Health, Bilthoven, The Netherlands and co-sponsored by the World Health Organization.
Chapter 6. Some economic aspects of a calibration unit as a part of a reference systemChapter 7. Application of reference methods in ambient air monitoring programs; Chapter 8. Principles for air quality assessment by impact and background; Chapter 9. Real time validation of air quality data; Chapter 10. Air pollution measurement system in India; Chapter 11. Pan American air monitoring network; Chapter 12. Aerosol spectrometry with centrifuges; Chapter.
Includes bibliographical references.
Print version record.
Elsevier
Keywords: Air -- Pollution -- Measurement -- Congresses; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Air -- Pollution -- Measurement; Electronic books